Using Virtual Reality to Complement Traditional Wheelchair Skills Training Methods: A Literature Review - Chantal Zorzi; Alexandra Covaci; Gianluca Marcelli (Applied Sciences)
Training wheelchair skills are vital for enhancing independence and safety. Traditional training methods require significant time and resources, limiting accessibility. Virtual reality (VR) offers an innovative solution by simulating real-life environments for training, reducing risks and costs. However, the effectiveness of VR in complementing real-life training remains underexplored. This review investigates how VR can complement traditional wheelchair training by assessing the strengths and limitations of existing VR systems. A literature review of 28 studies on VR applications for wheelchair training from 2017 to 2024 was conducted, focusing on studies that detailed VR environments and training programs. It was found that most VR systems were designed for powered wheelchair users with joystick navigation. VR environments included tasks from basic navigation to complex real-world scenarios. While VR showed potential in improving skills and engagement, challenges included the lack of standard methods for evaluating effectiveness and cybersickness. Overall, VR can be a valuable complementary tool for wheelchair training, especially for powered users. Future research should standardise protocols, and address side effects.